Development and Validation of a Self-care Scale for Clinical and Counseling Doctoral Students - (:unkn) unknown (My University, 2017)
Self-care is a critical component and considered a core foundational competency for doctoral students in the field of psychology. It is an ethical imperative to maintain adequate self-care in order to prevent burnout and negative outcomes to those receiving our healthcare services. Self-care is also related to the professional values of psychology, specifically beneficence and nonmaleficence which relates to our duty of exercising good judgment to avoid harm to clients. Despite being identified as such little research has explored the topic. One reason that may contribute to the lack of research is the need for a measure self-care behaviors. In this study, I sought to develop and evaluate a psychometric instrument to assess clinical and counseling doctoral students’ practice of self-care. The sample included a total of 232 current doctoral students in APA-accredited programs across different stages of the developmental trajectory. A pilot study was used for feedback on item content and suggestions for refinement with a sample of 28 clinical and counseling students from two APA-accredited programs. Participants received a $25 gift card as a token of appreciation for their time. In the full study, participants completed an online survey including a demographics form, the refined self-care measure, Maslach Burnout Inventory (emotional exhaustion, depersonalization, and personal accomplishment), Flourishing, Perception of Competence Scale, and a Distress Inventory. Participants received a $5 gift card as a reward. Internal consistency estimates were measured using Cronbach’s alpha for all measures: self-care scale ( = .83), burnout scales ( = .84EE, .79DEP, .87PA), well-being ( = .84), perceived competence (a = .88), and distress ( = .82). Convergent and discriminant validity was examined through the evaluation of self-care with all other instruments used. Exploratory factor analyses revealed a three-factor model with cognitive-emotional/relational, physical, and spiritual components underlying the construct of self-care. Bivariate correlations were conducted to understand relationships between self-care and other constructs in this study. Due to the training context of this study, post-hoc analyses revealed no significant differences between the three developmental stages in mean global scores of self-care. Limitations of the current study and implications for future research and practice are discussed.
Keywords: Doctoral Students; Instrument; Professional Psychology; Self-care; Training